INTEGRATING LIFE SKILLS IN ENGLISH LANGUAGE TEACHING (ELT): STRATEGIES, PROBLEMS AND THEIR POSSIBLE SOLUTIONS - -, Sajidin; Nurkamto, Joko; Saleh, Mursid; -, Retmono (Universitas Negeri Semarang, 2013)
The integration of life skills in English language teaching has to be managed properly to achieve an optimal result. The exploration to the fields reveals some problems on their implementation: (1) classroom management, (2) selection of learning materials, (3) learning assessment, and (4) selection of learning methods. In addition, most teachers were fully satisfied with the existing model due to the following reasons: (1) requiring an extra preparation and teaching media, (2) incomplete communication task executions, and (3) inflexibility of model to apply in any class. To make the model of implementation better some recommendation are made: (1) incorporating materials reflecting life skills, (2) providing more comprehensible inputs, (3) developing a representative assessments, and (4) selecting a learning method that guide teacher to gradually develop communicative competence and simultaneously develop life skills.